Assessment of the Relationship between Diabetic Retinopathy and Nailfold Capillaries in Type 2 Diabetics with a Noninvasive Method: Nailfold Videocapillaroscopy - Seyit Uyar; Ayşe Balkarlı; Muhammet Kazım Erol; Bayram Yeşil; Abdullah Tokuç; Doğan Durmaz; Süheyla Görar; Ayhan Hilmi Çekin (Journal of Diabetes Research)
Background and Objectives. Nailfold capillaroscopy is an easy and noninvasive technique used to investigate dermal microvasculature. Traditional investigations of vascularity do not detect changes until they are well-established in type 2 diabetics. The objective of the current study was to evaluate nailfold capillaries in type 2 diabetes mellitus patients and to determine the association of retinopathy with changes in the nailfold capillaries. Materials and Methods. Capillaroscopic findings by nailfold capillaroscopy and fundoscopic examinations were assessed in 216 patients with type 2 diabetes mellitus and 101 healthy controls included in this prospective study. Results. Retinopathy was detected in 43.05% of diabetic patients (n=93). Capillaroscopic findings including tortuosity (p<0.001), bushy capillary (p<0.001), neoformation (p<0.001), bizarre capillary (p<0.001), microhemorrhage (p=0.001), capillary ectasia (p=0.002), and aneurysm (p=0.004) were significantly higher in diabetic group than control group. In logistic regression analysis, only tortuosity was shown significant (OR, 2.16; p=0.036). There was also a significant relation between diabetes duration and most of the capillaroscopic findings. Conclusion. Capillaroscopic changes were found to be correlated with diabetic retinopathy, in particular with longer disease duration in our study. Capillaroscopic imaging could be a useful new technique for assessment of diabetic microvascular changes.